WALI NAGARI PEREMPUAN DI ERA REFORMASI: STUDI KASUS TERPILIHNYA WALI NAGARI BATU BASA KECAMATAN PARIANGAN KABUPATEN TANAH DATAR TAHUN 2009 - Iskandar, Israr (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2011)
This article attempts to describe the role and the pursuit of women’s leadership in Nagari (the villages) in West Sumatra. The issue is related to success of women appeared as Wali Nagari (Nagari’s formal leader) in the Era of Reform with a case study of Wali Nagari Batu Basa in Dictrict Tanah Datar. The victory of Bariana Sain, a middle-aged woman, even in a direct election in 2009, as a wali nagari Batu Basa are a new chapter in political history of women in West Sumatra. Previous elections with representative system at Nagari’s People’s Representative Council (BPRN) tends to choose men as wali nagari. However, democratization in the Reform Era have influenced the “perception” of local community towards women’s leadership. A victory of women as formal leaders in the Nagari Batu Basa was not only reflection of an egalitarian attitude of society, but also the competence of the women figure. Another winning factor is, of course, also related to the declining her rivals popularity, including incumbent.